T-Shaped Compact Dielectric Resonator Antenna for UWB Application - Zitouni, A.; Boukli-Hacene, N. (Advanced Electromagnetics, 2019)
In this article, a novel T-shaped compact dielectric resonator antenna for ultra-wideband (UWB) application is presented and studied. The proposed DRA structure consists of T-shaped dielectric resonator fed by stepped microstrip monopole printed antenna, partial ground plane and an inverted L-shaped stub. The inverted L-shaped stub and parasitic strip are utilized to improve impedance bandwidth. A comprehensive parametric study is carried out using HFSS software to achieve the optimum antenna performance and optimize the bandwidth of the proposed antenna. From the simulation results, it is found that the proposed antenna structure operates over a frequency range of 3.45 to more than 28 GHz with a fractional bandwidth over 156.12%, which covers UWB application, and having better gain and radiation characteristics.